UPAYA MEMACU PERTUMBUHAN TUNAS MIKRO KENTANG KULTIVAR GRANOLA DENGAN JENIS DAN KONSENTRASI SITOKININ BERBEDA - Adinda RN Pratama; Sugiyono Sugiyono; Lucky Prayoga; Ali Husni (Scripta Biologica, 2014)
Micro-shoot growth is the first step in the potato microtuber formation. The main factors were known controlling microtuber formation including the media type, the concentration of sucrose, the type and concentration of plant growth regulators, temperature, and photoperiodicity. This research aimed to determine the influence of the t of cytokinin and its concentration on the micro-shoot formation of Granola cultivar of potato (Solanum tuberosum L.), as well as to determine the best cytokinin type and its concentration on micro-shoot formation of Granola cultivar potato (Solanum tuberosum L.). The research was experimental in a split-plot design. The main plot was the type of cytokinin (BAP and Kinetin), and the subplot was cytokinin concentration at five levels of concentrations, i.e., 0, 5, 10, 15 and 20 µM. This study replicated each treatment three times which resulted in obtaining 30 experimental units. The data obtained were then analyzed using an analysis of variance, followed by honest significant difference test at 95 and 99% levels of confidence. The results showed that the formation of micro-shoot of Granola cultivar of potato was controlled by the type and concentration of cytokinin used. The addition of 5‒15 μM of BAP was found to be the best treatments to stimulate micro-shoot formation of Granola cultivar of potato.